2016
DOI: 10.1158/1078-0432.ccr-15-2762
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Plasma Cells Are Associated with Tertiary Lymphoid Structures, Cytolytic T-Cell Responses, and Superior Prognosis in Ovarian Cancer

Abstract: Purpose: CD8+ tumor-infiltrating lymphocytes (TIL) are key mediators of antitumor immunity and are strongly associated with survival in virtually all solid tumors. However, the prognostic effect of CD8+ TIL is markedly higher in the presence of CD20+ B cells, suggesting that cooperative interactions between these lymphocyte subsets lead to more potent antitumor immunity. Experimental Design: We assessed the colocalization patterns, phenotypes, and gene expression profiles of tumor-associated T- … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
335
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(404 citation statements)
references
References 50 publications
20
335
2
4
Order By: Relevance
“…Increased plasma cell density has been reported to be related to improved outcome in non-small cell lung cancer (NSCLC) and high-grade ovarian carcinoma (7,21), while other studies showed an association with higher tumor grade and reduced OS in ovarian cancer (22).…”
mentioning
confidence: 99%
“…Increased plasma cell density has been reported to be related to improved outcome in non-small cell lung cancer (NSCLC) and high-grade ovarian carcinoma (7,21), while other studies showed an association with higher tumor grade and reduced OS in ovarian cancer (22).…”
mentioning
confidence: 99%
“…Type 4 aggregates contain very few T-cells, but have well-formed GCs containing CD20 + B cells and CD21 + fDCs. In our study, we defined TLS as lymphoid aggregates with well-formed GCs, which included Type 3 and Type 4 lymphoid aggregates similar to those described in ovarian cancer by Kroeger and colleagues [21].…”
Section: Resultsmentioning
confidence: 97%
“…1). We followed the recently reported classification criteria for lymphoid aggregates based on size, cellular composition and degree of organization to define the types of TLS in the cohort under study [21]. Type 1 aggregates are small, compact, T-cell predominant lymphoid aggregates without apparent follicular structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations